"Are all diseases dead": The Likelihood of an Attribution to Ben Jonson. Issue 2 (November 2020) - Wiendels, Christina
Abstract : Arents S288 (Acc. No. 5442), pp. 87–88, and Rosenbach 239/27, p. 327, attribute the poem that begins "Are all diseases dead nor will death say" to Ben Jonson. While A.S.W. Rosenbach (1876–1952) owned both of these manuscripts at one point, it was actually Edwin Wolf 2nd (1911–1991) who penciled in the Jonson attributions in both manuscripts. However, the poem is found in many other manuscripts without this attribution. This paper considers the origin and validity of Wolf's attribution, and then asks, apart from Wolf's attribution, if it is plausible that Jonson wrote the poem. Wolf's consistently correct attributions in Arents S288 and correct attribution in MS 239/27 indicate that he was not as unreliable as the Rosenbach Museum & Library suggests. Ludovick Stuart, the Duke of Lennox and Richmond, who is the subject of the poem, died on 16 February 1624. My research demonstrates that an attribution to Jonson is highly plausible in terms of biographical, manuscript, and stylistic evidence. Jonson knew the poem's subject: he lived with the Duke's brother, Esmé Stuart, Lord d'Aubigny, for many years, and d'Aubigny occupied the role of patron. While the poem is elsewhere attributed to Sir John Eliot (b. 1592) or John Donne, neither is a strong candidate. The Duke fulfills the categories that I establish as Jonson's motivations to write in this poetic form: he was a significant figure and he had a personal connection to Jonson. Moreover, Jonson wrote for d'Aubigny's family on repeated occasions – and at length – over many decades.